MOLECULAR CHARACTERIZATION OF FLIC GENE BY SEMI NESTED PCR FOR THE DETECTION OF SALMONELLA ENTERICA SEROVAR TYPHI IN THE PERIPHERAL BLOOD OF PATIENTS FROM CHENNAI, INDIA - M. SOWMIYA; J. MALATHI; P. AARTHI; T. VAIDEHI; H. N. MADHAVAN (International Journal of Pharma and Bio Sciences, 2013)
Typhoid fever caused by Salmonella enterica serovar typhi (S. enterica serovar typhi) is one of the important public health problems in many developing countries. Conventional blood culture is currently the gold standard for diagnosis of typhoid fever by this bacterium, but it is time-consuming requiring several days for isolation of bacterium resulting in delay to initiate proper antibiotic therapy and often they are not cultivable. Early diagnosis of the disease is required since 2 to 5% of all deaths in India are due to typhoid fever. Semi-nested polymerase chain reaction (Sn-PCR) specific for the S. enterica serovar typhi targeting flagellinC (fliC) gene was standardized and applied onto 100 blood specimens. Sn-PCR was specific to S. enterica serovar typhi and sensitivity is 10fg/10μl of peripheral blood DNA. Positivity rate was 62% in culture negative specimens and 100% in culture positives (p=0.001). Sn-PCR was highly reproducible and could detect S. enterica serovar typhi in less than 12-24 hours after the receipt of the specimen in the laboratory and thus helping in rapid initiation of antibiotic treatment.